Concomitant occurrence of acneiform eruption, alopecia areata, and urticaria during adalimumab treatment in a patient with pustulosis palmoplantaris: Case report and literature review - Guan-Yi He; Tsen-Fang Tsai (Wolters Kluwer Medknow Publications, 2012)
Adalimumab is a fully human immunoglobulin G1 monoclonal antibody against tumor necrosis factor (TNF)-α that is increasingly used for the treatment of many autoimmune diseases. However, it has also been reported that adalimumab can induce many adverse cutaneous reactions, including paradoxical psoriasiform eruptions. We describe a patient with pustulosis palmoplantaris who developed four cutaneous adverse reactions, including eczematous lesions, acneiform eruption, alopecia areata, and urticaria during adalimumab treatment. A common histopathological finding in these acneiform and urticarial lesions was the presence of eosinophilic infiltrates. Some authors assume that cross-regulation between TNF-α and interferon-α may contribute to development of a clinical spectrum of cutaneous reactions in predisposed individuals undergoing anti-TNF therapy. The use of different biologics, including adalimumab, etanercept, and ustekinumab, did not seem to improve pustulosis palmoplantaris disease activity in our patient.